Studies of Mistletoe Presence on Five Tree Species of Samaru Area, Nigeria - Dlama, Tizhe Tari; Oluwagbemileke, Alonge Samson; Enehezeyi, Aliyu Ramatu (Recent Progress in Plant and Soil Research Vol. 1, 2021)
The infestation of trees by mistletoe is such that urgently call for attention as they reduce the vigor of trees growth and reproduction. In Samaru, a very little or no records is found on the type of mistletoe species found parasitic on tree species. In order to document and know the species richness of mistletoe within this region, the study was aimed at determining the different species of mistletoe parasitic on Albizzia lebbeck, Citrus grandis, Khaya senegalensis, Terminalia mantaly and Terminalia catappa within Samaru, Nigeria. The study site was divided into four sampling areas based on the presence of the studied species, and the infection of the trees by mistletoes. In each of the sampling areas, the leaves of mistletoes found parasitic on each of these tree species were collected. The study indicated that from all the sampling areas, A. lebbeck was infected by six different species of mistletoe: Tapinanthus dodoneifolius, Tapinanthus globiferus, Globimetula braunii, Globimetula oreophila, Englerina lecardii and Tapinanthus belvisii; C. grandis, T. catappa and T. mantaly each had four different species found parasitic on them, and K. senegalensis had three different mistletoes species parasitic on it. A. lebbeck had the highest number of different mistletoe species found parasitic on it while K. senegalensis had the lowest. G. braunii and T. globiferus were the most common mistletoe species found parasitic on all the targeted host trees while T. dodoneifolius was found parasitic only on A. lebbeck and T. catappa and E. lecardii was found parasitic only on A. lebbeck and C. grandis respectively in the study area. In conclusion, among the studied tree species, A. lebbeck was the most vulnerable to mistletoe attack in the study area and G. braunii and T. globiferus were less host specific.